La manualistica storico pedagogica dal passato al futuro - Salis, Marco (Studi sulla Formazione/Open Journal of Education, 2019)
The article offers an analysis of historical pedagogical manuals in Italy: most of the current texts fulfill the primary task of exposing the contents of the discipline in an orderly and essential manner and and they they contribute to the acquisition of an awareness of the main points of view on pedagogy.